In Vivo Immunostaining of Hemocyte Compartments in Drosophila for Live Imaging - Csordás, Gábor (Public Library of Science, 2014)
In recent years, Drosophila melanogaster has become an attractive model organism in which to study the structure and development of the cellular immune components. The emergence of immunological markers greatly accelerated the identification of the immune cells (hemocytes), while the creation of genetic reporter constructs allowed unique insight into the structural organization of hematopoietic tissues. However, investigation of the hemocyte compartments by the means of immunological markers requires dissection and fixation, which regularly disrupt the delicate structure and hamper the microanatomical characterization. Moreover, the investigation of transgenic reporters alone can be misleading as their expression often differs from the native expression pattern of their respective genes. We describe here a method that combines the reporter constructs and the immunological tools in live imaging, thereby allowing use of the array of available immunological markers while retaining the structural integrity of the hematopoietic compartments. The procedure allows the reversible immobilization of Drosophila larvae for high-resolution confocal imaging and the time-lapse video analysis of in vivo reporters. When combined with our antibody injection-based in situ immunostaining assay, the resulting double labeling of the hemocyte compartments can provide new information on the microanatomy and functional properties of the hematopoietic tissues in an intact state. Although this method was developed to study the immune system of Drosophila melanogaster, we anticipate that such a combination of genetic and immunological markers could become a versatile technique for in vivo studies in other biological systems too.